IBN ARABI'S CREATIVE IMAGINATION IN ODHY POETRY OF SUFISM FIGURES IN HIS ANTHOLOGY RAHASIA SANG GURU SUFI - Fuad, Khairul; Satriawan, Lalu Agus; Mashuri, Mashuri; Ma'arif, Syamsul; Harapandi, Harapandi (Islam Futura, 2023)
This research aims to analyze the Sufism figure in Odhy poetry anthology Rahasia Sang Guru Sufi through Ibn Arabi's creative imagination. The Sufism figure has an important role in the Sufism discourse, and creative imagination is related to literary discourse. Ibn Arabi’s creative imagination combined indicated Ibn Arabi himself and his imagination. Ibn Arabi’s thought is compatible with the literature and applied as a theoretical approach to mystical literature, namely the work of Odhy, the Sufism figure poetry. Those terms denote part and relate to Sufism studies, especially a murshid (guru) to guide the spiritual guidance through stations until the peak. Those path finders indicate the creative imagination that Odhy used in his poetry collection; at the same time, the literature has related to that imagination. This research reveals the mutual connection between literature and Islamic mysticism based on imagination. This figure is a person who wrote down his role in the discourse and history of Sufism. The data on Sufism figures are collected through the descriptive method from the primary source of those anthologies. Besides, the historical approach explains his poetries in those anthologies. This research found the Sufism figures as a thought in Islamic Mysticism in history through Ibn Arabi’s creative imagination and an image resource in literature.